Pengaruh Penerapan Model Pembelajaran Problem Based Learning Terhadap Hasil Belajar Siswa Materi Konsep Mol - Hiskia Wahongan; Sonny Lumingkewas (Oxygenius Journal Of Chemistry Education, 2022)
This research is an experimental study of Problem Based Learning model. This study aims to determine the effect of the Problem Based Learning learning model on student learning outcomes on the mole concept material. This research was conducted in class X SMA Negeri 1 Remboken with a total sample of 64 people. The research design used is an experimental method with a quantitative approach and the type of research used is a quasi-experimental research (Quasi Experimental design). The experimental class uses the Problem Based Learning model and the control class uses the conventional learning model. Analysis of hypothesis testing using t-test with a significant level of = 0.05 because, two-way test then the value of a/2 = 0.025. The test results obtained show that the results of tcount > ttable or 9.653 > 1.99897, thus H0 is rejected and H1 is accepted, this indicates that there is a significant difference between the average posttest scores of the experimental group and the control group. So it can be concluded that there is a difference between student learning outcomes using Problem Based Learning) and student learning outcomes using conventional learning models on the mole concept material.